(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract: The research aims to achieve the basis of tax justice by making a comparison between the tax accounting process according to the application of the International Financial Reporting Standard IFRS15 and the tax accounting procedures currently used in the General Authority for Taxes to determine the annual and total tax differences, to give credibility and enhance transparency in the reports and financial statements of companies Long-term contracts when prepared in accordance with the requirements of applying the international standard IFRS15 “Revenue from Contracts with Customers”, which increases the possibility of relying on them when calculating taxes. Thus, the research problem is how to achieve the tax justice base for the two parties to the tax accounting according to the adoption of the application of the international standard IFRS 15 by the long-term contracting companies, which makes the General Tax Authority account these companies annually according to what the financial statements show to reach the annual tax amount. The research is based on a basic hypothesis that adopting the application of the international standard IFRS 15 when conducting tax accounting achieves the basis of tax justice for long-term contracting companies and the public treasury of the state. After studying and analyzing the financial statements of some long-term contracting (construction) companies, the research showed a number of conclusions, the most important of which is that the application of the international standard IFRS 15 will not affect the total revenues, whether when applying the previous international accounting standards or the local accounting systems (the unified accounting system and the Iraqi accounting base No. / 1), but changes in the policy of its distribution over the life of the contract in conjunction with the fulfillment of the performance obligations of the contract, which contributes to achieving the tax justice base for the two parties to tax accountability, and the research also showed a number of recommendations, the most important of which is the necessity of applying the international standard IFRS 15 by long contracting companies The term, in order to contribute to the realization of the tax justice base when conducting the tax accounting process for construction companies to develop treatments for the obstacles that hinder the process of adopting the international standard IFRS15, through the study of laws, regulations and instructions that conflict with the application of the standard, on top of which is Income Tax Law No. 113 of 1982. (Amended).